An analysis of relative costs and potential benefits of different policies for antenatal screening for beta thalassaemia trait and variant haemoglobins. Issue 9 (1st September 1999) - Phelan, L; Bain, B J; Roper, D; Jury, C; Bain, K
Abstract : AIMS: To investigate the costs and potential benefits of different policies for antenatal screening for haemoglobinopathies in two multiethnic London communities. METHODS: 1000 consecutive antenatal patient samples referred to each of two London teaching hospital laboratories for haemoglobinopathy testing were investigated using the standard procedures of the laboratory in question. When the standard procedures did not include high performance liquid chromatography (HPLC), this technique was added, in order to assess its diagnostic value and cost-effectiveness. A comparison was made between the costs and potential benefits of universal testing for variant haemoglobins and beta thalassaemia trait using HPLC and the costs and potential benefits of universal testing for variant haemoglobins and selective testing for beta thalassaemia trait using the mean cell haemoglobin (MCH) as a screening test and less automated techniques than HPLC for definitive diagnosis. RESULTS: The costs of the two policies were found to be comparable, as the higher reagent/instrument costs of HPLC were offset by the lower labour costs. Universal testing of 2000 consecutive samples did not disclose any extra cases of beta thalassaemia trait which would not have been detected by universal screening and selective testing. However, six patients were found to have a haemoglobin A2 variant which can interfere with the diagnosis of beta thalassaemia trait. CONCLUSIONS: The introduction of universal testing by HPLC into British laboratories could be cost neutral and has potential benefits. If a higher cost is accepted then the greater degree of automation could be used to release skilled staff for other tasks within the laboratory.